Stress Field Control of Eruption Dynamics - Antonio Costa (Frontiers Research Topics, 2017)
Increasing evidence supports the claim that stress changes play a fundamental role in triggering volcanic eruptions. Stress changes may vary in origin to include earthquakes, erosion and landslide processes, deglaciation, or tidal effects. The local stress can also change as response of magma influx from deeper reservoirs and an increase of the magma/gas pressure. The stress transfer may be of great importance in reawakening a dormant system. As an example, significant statistical correlation of large earthquakes and eruptions in time and space was suggested in many works. The interaction may be two-fold; where magma intrusions may change the stress at active faults and trigger earthquakes, while tectonic earthquakes may affect the magmatic system and change the eruption activity. The change in local tectonic stress has been claimed as trigger of large ignimbrite eruptions or for controlling the eruptive style of explosive eruptions. Sometimes volcano systems that are nested or closely located may become active in chorus; neighbouring volcanoes may interact in the sense that one volcano triggers its neighbouring volcano. However, although there is ample evidence of concurrence, the processes of interacting volcanoes and near- to far-field tectonic stress are not well understood. Some studies suggest that volcanic eruptions are triggered if compressive stress acts at the magma system and "squeezes" out magma. Other studies suggest that extensional stress fields facilitate magma rise and thus encourage eruptions, or that fluctuating compression and extension during the passing of seismic waves trigger eruptions. This research topic tries to address some of the important open questions in interaction between stress field and volcanic eruption, though both review papers and new contributions.